Asymmetric Information, Financial Intermediation and the Monetary Transmission Mechanism: A Critical Review - Iris Claus; Arthur Grimes (New Zealand Government, The Treasury, 2003)
Macroeconomic models currently used by policy makers generally assume that the workings of financial markets can be fully summarised by financial prices, because the Modigliani and Miller (1958) theorem holds. This paper argues that these models are too limited in describing how monetary policy (and other) shocks are transmitted to the economy and points to new directions. The models are too limited because they disregard an information asymmetry between borrowers and lenders and the importance of financial intermediaries not only for individual depositors but the economy as a whole. Incorporating financial market interactions into macroeconomic models will enhance the understanding of the transmission mechanisms of monetary policy and other shocks.
Keywords: E32; E44; E50; 330; Financial intermediaries; credit channel; monetary transmission mechanism; open economies